El Excentrico, 1969-06-20 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
June 20, 1969 [20 de junio de 1969]. No volume or issue number. Cover has headshots of Actor Humberto, Parde Humberto. Below these head shots are group photographs of Sophia Loren & Actor Humberto and Hannah the Leper & Humberto.